저온플라즈마(Microwave Plasma)를 활용한 Acidovorax citrulli 감염 수박종자의 살균 효과 검정 - 김상우(Sang Woo Kim); 주한준(Han Jun Ju); 권병헌(Byeong Heon Gwon); 마헤시 아드히카리(Mahesh Adhikari); 김현승(Hyun Seung Kim); 박미리(Mi-Ri Park); 이윤수(Youn Su Lee) (Sigmulbyeong yeon'gu, 2021)
This study was conducted to check the sterilization efficacy of microwave plasma (MWP) against the watermelon seeds infected with Acidovorax citrulli 11-251. Watermelon seeds were artificially vacuum inoculated to produce A. citrulli 11-251 infected seeds. Aac ImmunoStrip and scanning electron microscope (SEM) results suggests that, seeds (coat and endosperm) were infected under the concentration of 1×107/30 min. MWP sterlization process was carried out at 50 W (3 min, 5 min, and 10 min), 80 W (3 min, 5 min, and 10 min), and 100 W (3 min, 5 min, and 10 min). According to the results, MWP sterilized the artificially inoculated seed coats by 95.96% at 80 W/10 min and seed endosperms by 100% at 100 W/10 min respectively. Although, seeds were sterlized by MWP, germination rate of seeds were low as compared to non treated (negative control) seeds. Moreover, cell membrane of A. citrulli 11-251 was damaged while observed in SEM after sterilized with MWP. Further studies regarding the appropriate sterilization condition by MWP against A. citrulli infected seeds for germination will be conducted in our next study. 본 연구에서는 마이크로웨이브 플라즈마(microwave plasma)를 이용하여 종자에 감염된 Acidovorax citrulli 11-251의 살균효과를 확인하였다. 감압처리를 통하여 수박 종자에 A. citrulli 11-251를 인공접종하여 이병 종자를 제작하였으며, Aac ImmunoStrip및 scanning electron microscope 확인 결과, 종피 및 종자 내부에 1×107/30분 처리한 조건에서 감염되었음을 확인하였다. 플라즈마 처리는 50 W (3분, 5분, 10분), 80 W (3분, 5분, 10분), 100 W (3분, 5분, 10분) 조건으로 실험 결과, 인공감염종자를 플라즈마 처리 시 대조구와 비교해보면 종피의 경우 80W/10분, 99.56%의 살균 효과를 보였고, 종자 내부는 80 W, 100W/10분, 100%의 높은 살균 효과를 보였다. 인공접종 종자를 사용하여 플라즈마 살균장치의 종자살균 효과를 확인하였다. 하지만 발아율은 무처리구보다 플라즈마 처리 시 급격히 떨어지는 것을 확인하였다. 주사전자현미경 관찰 결과, 플라즈마 처리가 A. citrulli 11-251의 세포막을 파괴하는 것을 확인하였다. 또한, A. citrulli가 접종된 수박 종자를 이용하여 플라즈마 처리 시 살균 및 발아율을 높일 수 있는 최적 조건에 대한 추가 실험이 수행될 예정이다.